The Influence of CEO Power Characteristics and Chief Sustainability Officer on ESG Performance - Desy Kalfira; Shanti (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
After the Covid-19 pandemic, global companies have faced complex challenges that drive a paradigm shift from a financial focus to social and environmental sustainability. ESG scores serve as an important indicator in assessing corporate sustainability. This study provides an important contribution due to the limited number of studies in Indonesia that examine ESG performance rather than merely ESG disclosure, which allows the results to better reflect the quality of sustainability implementation. This research employs a quantitative approach to analyze the effects of CEO education, ownership power, CEO tenure, and the presence of a CSO on ESG performance, with profitability and firm size as control variables. The research data consist of secondary data from companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period, selected using purposive sampling and analyzed using multiple linear regression with SPSS 30. The findings show that CEO education and ownership power have no significant effect on ESG performance, while CEO tenure and CSO have a significant effect on ESG performance. Companies that establish a CSO demonstrate a proactive approach to addressing ESG issues. This study evaluates the role of CSO which remains underexplored, suggesting that regulators, particularly the OJK, should encourage public companies to position the CSO as a strategic role in presenting ESG scores as part of transparency and accountability in supporting the SDGs.